Pengujian Pasar Efisien dan Single Index Model pada Peristiwa Pengumuman Kenaikkan Harga BBM di Bursa Efek Indonesia - Hidayat, Riskin (potensio, 2008)
This study aimed to test the efficiency of capital marketsand the Single Index Model in Indonesia, related to the announcementof fuel price rise on May 24, 2008. The samplein this study as many as ten stocks listed on the IndonesiaStock Exchange (IDX) and actively traded on 10 (ten) daysbefore and 10 (ten) days after the announcement of fuel pricerise on May 24, 2008, or by a window period of 21 days. Theresults showed that in the event that the announcement offuel price increases announced by the government on May24, 2008 are no differences in average abnormal return ofbetween 10 (ten) days before and 10 (ten) days after theannouncement. In periods of negative abnormal return observationsoccurred before the announcement of fuel priceincreases, which means there have been leaks of information,where the issue of fuel price increases have been informedby the previous government. This shows that the Indonesiancapital market is not efficient in this case. The studyalso found that the SIM does not apply to the period of observation,because of the variability of the beta is not followed bythe variability of stock returns or in other words there is nolinear relationship between beta and returnKey Word: Efficiency of capital markets, Single Index Model